PERAN ARUS KAS OPERASI, BOOK TAX DIFFERENCES DAN KEPEMILIKAN MANAJERIAL DALAM PERSISTENSI LABA SUBSEKTOR PERBANKAN - Jannati, Nur; Wibowo, Agus Satrya; Setiawan, Ricky Yunisar (STIE Mahardhika, 2025)
The purpose of this research is an influence of operating cash flow, book tax differences and managerial ownership on Earning Persistences. The population in this study are banking companies listed on the Indonesia Stock Exchange (BEI) in 2022-2023. The samples in this study were 16 companies for 2 periods. The research method used is quantitative with secondary data sources. The sampling technique uses purposive sampling method. The methode of data analysis uses multiple linear regression analysis with SPSS version 27. Simultaneously, the operating cash flow variable, book tax differences and managerial ownership have a significant effect on earnings persistence. The results of this study provide empirical evidence that partially the operating cash flow variable has a significant negative effect on earnings persistence and the book tax differences variable has a positive effect on earnings persistence. Meanwhile, the managerial ownership variable has no effect on earnings persistence.